High charge mobility polymers based on a new di(thiophen-2-yl)thieno[3, 2-b]thiophene for transistors and solar cells. Issue 44 (18th September 2015) - Chen, Lie; Wu, Feiyan; Deng, Zhiqiang; Feng, Linlin; Gu, Pengcheng; Dong, Huanli; Hu, Wenping; Chen, Yiwang
Abstract : A novel random copolymer of di(thiophen-2-yl)thieno[3, 2- b ]thiophene (DTTT) with DPP achieved a high hole mobility of 0.627 cm 2 V −1 s −1 . Abstract : A novel donor–acceptor (D–A) donor di(thiophen-2-yl)thieno[3, 2- b ]thiophene (DTTT) was designed and synthesized according to the structure of the diketopyrrolopyrrole (DPP) acceptor. The random polymers with different ratios of DTTT/DPP, PDTTT-T-DPP_3/7 and PDTTT-T-DPP_4/6, and the alternating polymer PDTTT-DPP were synthesized through random copolymerization and direct arylation schemes respectively. Although the planarity of the DTTT structure is not as good as the DPP molecule, incorporation of DTTT and DPP molecules stimulates the polymers to achieve a high hole mobility, as determined by polymer thin film transistor (PTFT) devices, as well as yield fine power conversion efficiencies in polymer solar cells. Especially for PDTTT-T-DPP_3/7, the PTFT devices obtain a high hole mobility of 0.627 cm 2 V −1 s −1 . The results demonstrate that DTTT-T-DPP based random polymers are promising candidates for various high-performance organic electronic devices. Moreover, the strategy of designing new D/A molecules on the basis of high-performance structures is proved to be effective.